1989
DOI: 10.1073/pnas.86.17.6719
|View full text |Cite
|
Sign up to set email alerts
|

Selective changes in expression of HLA class I polymorphic determinants in human solid tumors.

Abstract: Analysis of surgical biopsies with monoclonal antibodies (mAbs) to framework determinants of major histocompatibility complex class I antigens has shown that malignant transformation is frequently associated with a marked loss of these cell surface molecules. The present study sought to determine whether more selective losses of major histocompatibility complex class I expression occur. Multiple specimens from 13 different types of primary and metastatic tumors were tested utilizing mAb BB7.2, which recognizes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
2

Year Published

1995
1995
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(54 citation statements)
references
References 26 publications
4
48
2
Order By: Relevance
“…2b) showed an almost complete downregulation of HLA-C [measured using mAb L31 (Grassi et al, 1991;Setini et al, 1996), which is specific for HLA-C open conformers]. The bulk of MHC class I, measured by mAb W6/32 (Natali et al, 1989), specific for all trimericconformation class I molecules, showed a reduction compatible with the silencing of HLA-C and the conservation of HLA-A and -B, as already seen by RNA analysis. Among the HIV-1 receptors, CD4 and CXCR4 expression was unaltered by the treatment, whilst CCR5 shows a minor reduction in expression (not evidenced by RNA analysis).…”
Section: Hla-c Sirna Silencing In Cell Linesmentioning
confidence: 81%
See 1 more Smart Citation
“…2b) showed an almost complete downregulation of HLA-C [measured using mAb L31 (Grassi et al, 1991;Setini et al, 1996), which is specific for HLA-C open conformers]. The bulk of MHC class I, measured by mAb W6/32 (Natali et al, 1989), specific for all trimericconformation class I molecules, showed a reduction compatible with the silencing of HLA-C and the conservation of HLA-A and -B, as already seen by RNA analysis. Among the HIV-1 receptors, CD4 and CXCR4 expression was unaltered by the treatment, whilst CCR5 shows a minor reduction in expression (not evidenced by RNA analysis).…”
Section: Hla-c Sirna Silencing In Cell Linesmentioning
confidence: 81%
“…VSV-G env and the HIV-1 env and rev sequences of the HIV-1 subtype B strains QH0692.42, AC10, 6535.5 and pRHPA4259.7 and subtype D strain NDK were obtained through the MRC CFAR NIBSC programme. mAbs L31 (Grassi et al, 1991;Setini et al, 1996) and W6/32 (Natali et al, 1989) were provided by Dr P. Giacomini (Laboratory of Immunology, Regina Elena Cancer Institute CRS, Rome, Italy). mAb M01 16/4/1 (anti-p24) was donated from Polymun, Germany.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the well-recognized tumor immune evasion mechanisms include failure of tumor antigen recognition (4-6), modulation of MHC molecule expression (7,8), improper activation of antigen-presenting cells (APC; refs. 1, 9), failure of lymphocyte homing (1,10), and production of immunosuppressive cytokines (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…12 Immunohistochemical (IHC) studies in different types of solid tumors have demonstrated defects in HLA class Ia expression. 13 Moreover, selective down-regulation of the HLA class I A or B locus also has been observed in GC, colon carcinoma, and laryngeal carcinoma. 14,15 However, most IHC studies of functional HLA expression on tumor samples have been performed with either monomorphic-determinant and/or allele-specific antibodies directed against HLA class Ia, because locusspecific antibodies are not available commercially.…”
mentioning
confidence: 99%